I’JAZ AL-QUR’AN DALAM PANDANGAN ULAMA’ MU’TAZILAH PADA KONSEP AL- SARFAH - Vidia Alfisyahri Ramadhani; Abdul Aziz Hasibuan, Habib Zikri, Harun Ar-Rasyid (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The purpose of this article is to explain the I'jaz of the Qur'an from the the concept of Al- Sarfah which was the origin of mu'tazilah ulama'. I'jaz Al-Qur'an according to Mu'tazilah scholars is an event that weakens anyone who challenges the Al-Qur'an. Al-Sarfah's ideology explains about the I'jaz of the Qur'an that miracles arise not from internal factors but from external factors. This research uses analytical qualitative methods with literature review. The findings in this research are that there are advantages to the Al-Sarfah in the study of I’jaz Al-Qur’an, namely in the context of interpreting the Al-Qur’an and relevance between Al-Sarfah and I’jaz Al-Qur’an.